A computer-aided design tool to facilitate the realisation of cooling systems. (27th July 2009) - Fok, S.C.; Tan, F.L.
In electronic products that require cooling management, the cumbersome task of finding suitable commercial thermoelectric cooler modules and determining their performances in the designs can often slow down the product realisation process. This paper presents a framework and an internet-enabled computer-aided design tool to assist designers in cooling system development. Based on user design specifications, the product design facility can estimate the required heat load, determine the required component characteristics, search for appropriate parts from different vendors and analyse the thermal performances of user-selected modules in cooling system designs. These facilities will allow designers to develop Thermoelectric Cooling (TEC) systems in less time using the latest and most suitable thermoelectric components available on the market.